1997
DOI: 10.1097/00000433-199712000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Year Review of Railway-Related Deaths in Jefferson County, Alabama

Abstract: A retrospective computer search of the records of the Jefferson County Coroner/Medical Examiner Office covering the 15-year period from 1981 to 1995 revealed 86 cases in which either a train caused death or in which a body was found dead by the tracks. The average age of the decedents was 39 years (range, 3 weeks-87 years). Men accounted for 88% of the deaths. The manners of death were as follows: three natural, 64 accident, seven suicide, six homicide, and six undetermined. Six decedents were found dead by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 4 publications
7
16
1
3
Order By: Relevance
“…Sex and age distributions are also similar to other studies [1,5,9,11,12,13]. Most victims, in both categories, are men and usually middle-aged in suicides while younger in accidents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Sex and age distributions are also similar to other studies [1,5,9,11,12,13]. Most victims, in both categories, are men and usually middle-aged in suicides while younger in accidents.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies describe the frequency and characteristics of railway suicide in different countries [5,6,7,8,9,10,11,12,13], but only few of them explore systems-oriented preventative possibilities in more detail [14,15], mostly with reference to underground systems [16,17]. Our findings on victims awaiting trains on site and the nearness between place of occurrence and place of residence are in line with findings from other studies [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the often arduous reconstruction of the circumstances leading up to the event and the medico-legal differential diagnosis between suicide, homicide, accident or running over of a corpse, the evidence gathered at the scene and during the autopsy is of utmost importance (Murphy, 1976;Messina, 1992;Cina et al, 1994;Davis et al, 1997;Lerer and Matzopoulos, 1997;Cicognani and Landuzzi, 1998;Ventura et al, 2004;De Giorgio et al, 2006;Mohanty et al, 2007;Zoja et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to well-documented automated protection devices, e.g. lights and bells (Ward & Wilde, 1995), the installation of well-known techniques such as crossing guard-rails that cannot be circumvented may prove fruitful (Davis et al, 1997). Additionally, advanced warning and advisory signage for passive railway crossings have recently received favourably reviews (Ward & Wilde, 1995;Austin & Carson, 2002) and such countermeasures may further be enhanced if combined with emerging intelligent transportation initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, some risk-taking behaviours may occur due to a distorted sense of risk perception, as research has demonstrated that railway vehicle fatalities may be linked to drivers intentionally trying to beat the train to the crossing (Davis, Alexander & Brissie, 1997). This may be seen to occur when young drivers knowingly engage in what amounts to dangerous behaviour, mistakenly assuming it to be low risk.…”
Section: Current Contextmentioning
confidence: 99%